Prospective evaluation on the use of geoprocessing in the study of dengue cases (Research, Society and Development, 2022)
Dengue has spread rapidly through several regions in recent years, leading to the emergence of epidemics. In this context, geoprocessing has great applicability, as it helps in monitoring, evaluation and planning in situations of epidemiological risk. The objective was, therefore, to carry out a prospection based on the search for scientific articles on the use of geoprocessing in the study of dengue cases. The research was of an exploratory documentary type, with searches for articles published between 2010 and 2020 in Science Direct, PubMed, Scielo, Web of Science and Google Scholar. To refine the search, specific terms, Boolean operators and truncation techniques were used in the abstract, title and keywords. Articles that used geoprocessing in dengue case studies were selected. 398 articles were found, of which 51 studies were published in 2020. Brazil was the country that stood out with the most publications. The ArcGis mapping program was the most used in the studies. Although dengue is a disease that affects many places, there is a lack of research on the use of geoprocessing related to the disease. This study showed that more research aimed at mapping dengue cases in endemic areas still needs to be carried out.